1983
DOI: 10.1002/anie.198308681
|View full text |Cite
|
Sign up to set email alerts
|

Thermolysis and Reactions of 4,5‐Benzotricyclo[4.1.0.01,3]hept‐4‐ene and o‐(Propadienyl)styrene

Abstract: influenced by the bridging; the conformation preferred in the crystal (see Fig. 2) is not crown-but saddle-shaped, as in 1,4,7-tro~onin['~]. Since the change in conformation in all these cases161 is not likely to require much extra energy, 3 and 4 may, like the parent system, be regarded as potential novel crown ether-like ligands for metal complexes. r 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This interaction should be reflected in the thermal behavior of these tricyclic olefins. Consistent with this notion, 4,5-benzotricyclo[4.1.0.0 1,3 ]hept-4-ene ( 3 ) dimerizes and rearranges to 2-methylnaphthalene at 30 °C 2c. It has been suggested that spiro tricycloheptene 2 has eluded isolation because of a facile [σ 2s + π 2s + σ 2s ] pericyclic rearrangement initially leading to 5-methylene-1,3-cyclohexadiene, which subsequently undergoes a hydrogen shift to afford toluene. 2b,c, Tricyclo[4.2.0.0 1,3 ]oct-4-ene ( 1 ) contains only an extra methylene group in comparison to tricyclo[4.1.0.0 4,6 ]hept-2-ene ( 2 ).…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…This interaction should be reflected in the thermal behavior of these tricyclic olefins. Consistent with this notion, 4,5-benzotricyclo[4.1.0.0 1,3 ]hept-4-ene ( 3 ) dimerizes and rearranges to 2-methylnaphthalene at 30 °C 2c. It has been suggested that spiro tricycloheptene 2 has eluded isolation because of a facile [σ 2s + π 2s + σ 2s ] pericyclic rearrangement initially leading to 5-methylene-1,3-cyclohexadiene, which subsequently undergoes a hydrogen shift to afford toluene. 2b,c, Tricyclo[4.2.0.0 1,3 ]oct-4-ene ( 1 ) contains only an extra methylene group in comparison to tricyclo[4.1.0.0 4,6 ]hept-2-ene ( 2 ).…”
Section: Introductionmentioning
confidence: 79%
“…Consistent with this notion, 4,5-benzotricyclo[4.1.0.0 1,3 ]hept-4-ene ( 3 ) dimerizes and rearranges to 2-methylnaphthalene at 30 °C 2c. It has been suggested that spiro tricycloheptene 2 has eluded isolation because of a facile [σ 2s + π 2s + σ 2s ] pericyclic rearrangement initially leading to 5-methylene-1,3-cyclohexadiene, which subsequently undergoes a hydrogen shift to afford toluene. 2b,c, Tricyclo[4.2.0.0 1,3 ]oct-4-ene ( 1 ) contains only an extra methylene group in comparison to tricyclo[4.1.0.0 4,6 ]hept-2-ene ( 2 ). Thus, in principle, tricyclo[4.2.0.0 1,3 ]oct-4-ene ( 1 ) could undergo an analogous pericyclic rearrangement which would thermally destabilize the system and, potentially, lead to the formation of spirobicyclo[5.2]octa-2,4-diene.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations